Android Studio 4.1 Development Essentials - Kotlin Edition - Smyth, Neil (Packt Publishing, 2021)
Acquire the skills necessary to develop Android apps using the Android Studio integrated development environment and the Kotlin programming language Key Features Learn to code using the Kotlin programming language Use the latest Material Design components to build modern user interface designs Integrate with SQLite databases and the Android Room Persistence Library Book Description Android 11 has a ton of new capabilities. It comes up with three foci: a people-centric approach to communication, controls to let users quickly access and manage all of their smart devices, and privacy to give users more ways to control how data on devices is shared. This book starts off with the steps necessary to set up an Android development and testing environment, followed by an introduction to programming in Kotlin. An overview of Android Studio and its architecture is provided, followed by an in-depth look at the design of Android applications and user interfaces using the Android Studio environment. You will also learn about the Android architecture components along with some advanced topics such as touch screen handling, gesture recognition, the recording and playback of audio, app links, dynamic delivery, the AndroidStudio profiler, Gradle build configuration, and submitting apps to the Google Play Developer Console. The concepts of material design are also covered in detail. This edition of the book also covers printing, transitions, and cloud-based file storage; foldable device support is the cherry on the cake. By the end of this course, you will be able to develop Android 11 Apps using Android Studio 4.1, Kotlin, and Android Jetpack. What you will learn Install and configure Android Studio on Windows, macOS, and Linux Write multi-threaded Kotlin code using Coroutines Understand Android architecture and app lifecycle Build view model-based apps using the Jetpack architecture Integrate your apps with Google cloud storage Add printing support from within your own apps Who this book is for This book is for Kotlin developers who want to learn essential skills to work with Android Studio 4.1 to build applications. The book also covers important topics about Android architecture essential for anyone looking to become an Android application developer. Assuming you already have some programming experience, are ready to download Android Studio and the Android SDK, have access to a Windows, Mac, or Linux system, and have ideas for some apps to develop, then you ...